Marriage and Economic Status as Predictors of Depressed Symptoms - Kautsar, Achmad; Widiani, Dini; Tarani, Ni Putu Mia; Wulandari, Grace; Siregar, Adiatma Y. M. (Economics and Finance in Indonesia, 2024)
Mental disorders can result in more significant economic losses than chronic physical illnesses. Mental disorders can be influenced by both economic and non-economic factors. This study investigates the influence of marital status and economic status interventions on depression symptoms with Propensity Score Matching (PSM). The data of this analysis was obtained from the Indonesian Family Life Survey (IFLS V). The findings indicated that individuals who were married experienced a 6% reduction in depressive symptoms, while those in the middle to high economic status category experienced a 3% decrease. Enhancing well-being and promoting effective communication play crucial roles in mitigating depressive symptoms.